Anger Is an Approach-Related Affect Evidence and Implications. [article]. - Carver, Charles S.
The authors review a range of evidence concerning the motivational underpinnings of anger as an affect, with particular reference to the relationship between anger and anxiety or fear. The evidence supports the view that anger relates to an appetative or approach motivational system, whereas anxiety relates to an aversive or avoidance motivational system. This evidence appears to have 2 implications. One implication concern the nature of anterior cortical asymmetry effects. The evidence suggests that such asymmetry reflects direction of motivationalengagement (approach vs. withdrawal) rather than affective valence. The other implication concerns the idea that affect s form a purely positive dimension and a purely negative edimension, which reflects the operation of appetative and aversive motivational systems, respectively. The evidence reviewed does not support that view. The evidence is, however, consistent with a discrete-emotions view (which does not rely on dimentionality) and with an alternative dimensional approach. -- (from the author)